Spectrum of Mutations in Chorionic Villous Samples for Prenatal Diagnosis of Thalassemia in Patients Presenting at a Tertiary Care Diagnostic Centre - Sardar, Annum; Robert, Helen Mary; Akhtar, Fahim; Mahmood, Asad; Ali, Sadia; Zahir, Saima (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the spectrum of mutations in chorionic villous samples (CVS) for prenatal diagnosis of thalassemia in patients presenting at a tertiary care diagnostic centre. Study Design: Cross-sectional study. Place and Duration of Study: Department of Hematology, Armed Forces Institute of Pathology (AFIP) Rawalpindi, Pakistan, from Jul 2020 to Jan 2021. Methodology: Chorionic villous sampling (CVS) was performed between the 12th and 16th weeks of pregnancy. A transabdominal technique was used to obtain placental specimen. The couples’ blood samples were collected in vials coated with ethylene diamine tetra acetic acid (EDTA). Chelex technique was used to extract genomic DNA. For genetic analysis of mutations, the Amplification Refractory Mutation System - Polymerase Chain Reaction (ARMS-PCR) was used. Results: A total of ninety-four women underwent chorionic villous sampling. After DNA analysis, β-thalassemia major was diagnosed in 18(18.9%), β-thalassemia trait found in 52(55.3%) cases and no mutation was detected in 24(25.5%) cases. Among the patients diagnosed with β-thalassemia major, 15(83.33%) were homozygous and remaining 3(33.33%) were compound heterozygous. Conclusion: Prenatal chorionic villous sampling and molecular analysis is useful in identifying β-thalassemia and β- thalassemia trait during pregnancy.